Sistem Pakar Mendiagnosa Penyakit Ayam Kampung Dengan Menggunakan Metode Certainty Factor Berbasis Web - Ida Royani Simanungkalit; Bosker Sinaga (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Poultry farming in Indonesia is still not successful in meeting some of the domestic needs, including being vulnerable to attacks by dangerous animal diseases. People are also restless because of dangerous diseases from chickens that can be transmitted to humans due to consuming chicken meat that has been infected with the disease. The case study in conducting research to diagnose free-range chicken disease was carried out at the Bang Ari Chicken Farm on Jalan Jamin Ginting Pamen Complex No.14 Padang Bulan, Medan Baru District, Medan City. The required criteria data is the type of disease and symptoms of the disease that attacks native chickens as well as the treatment actions that will be taken against the diseased chickens according to the disease experienced. This study aims to build a web-based expert system in diagnosing free-range chicken diseases using the certainty factor method. From the case example, the results of the calculation of certainty factor on the symptoms of free-range chickens, the disease that has the largest percentage value is P 7, namely Chronic Cough Disease of 97.50%. The system for diagnosing free-range chicken disease was built using a web-based programming language and MySQL database.